PENGEMBANGAN VIDEO PEMBELAJARAN VIDEOSCRIBE BERBASIS LITERASI SAINS DI SEKOLAH DASAR - Pipit Pitriyani; Aan Subhan Pamungkas; Trian Pamungkas Alamsyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Scientific literacy is one of the skills that should be mastered in the 21st century. This scientific literacy can be implemented though the learning media. The purpose of this study was to develop a learning video by using a science-based Videoscribe application. The model of development in this study was the five-step ADDIE model of refinement analysis, design, development, implementation and evaluation. Based on the validation from language, material and media experts, the average percentage of the learning videos was 89.7% with "very valid/ very worthy" category. The experimental stage of the study was carried out by as many as three phases of one to one, trial by small groups, and test by large groups. Students’ response to the science-based Videoscribe learning video on trial one to one obtained a percentage of 100% that was in "excellent" category. Students’ response to small group trials received an average of 96.25% in "excellent” category, and students' responses to large group trials received an average of 96.6% in "excellent " category. Whereas, the students’ science literacy test results in each test obtained a various value; one-on-one test obtained an average of 66.7% with "good” category. Small group testing got an average of 58.3% with "fairly good " category. Whereas, the large group trial got an average value of 57.3% that fell into "fairly good" category. It was concluded that scientific literacy based Videoscribe learning videos was suitable to be used in learning and it received a very good response from students. Besides, students’ understanding of science literacy material was also quite good.